2022
DOI: 10.1002/mp.16070
|View full text |Cite
|
Sign up to set email alerts
|

Dual imaging modality of fluorescence and transmission X‐rays for gold nanoparticle‐injected living mice

Abstract: Background: X-ray fluorescence (XRF) imaging for metal nanoparticles (MNPs) is a promising molecular imaging modality that can determine dynamic biodistributions of MNPs. However, it has the limitation that it only provides functional information. Purpose: In this study, we aim to show the feasibility of acquiring functional and anatomic information on the same platform by demonstrating a dual imaging modality of pinhole XRF and computed tomography (CT) for gold nanoparticle (GNP)-injected living mice. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The radiation dose delivered to the acrylic phantom with an acquisition time of 10 minutes per scan position and filtered incident X-ray spectrum would be ~3.26 Gy. This dose, although, is lower by a factor of two compared to the studies showing similar imaging detection limits [ 43 ], [ 44 ], is still relatively high for preclinical in-vivo applications [ 33 ], [ 48 ], [ 49 ]. Moreover, the long imaging time of the current system configuration further impedes its in-vivo applicability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiation dose delivered to the acrylic phantom with an acquisition time of 10 minutes per scan position and filtered incident X-ray spectrum would be ~3.26 Gy. This dose, although, is lower by a factor of two compared to the studies showing similar imaging detection limits [ 43 ], [ 44 ], is still relatively high for preclinical in-vivo applications [ 33 ], [ 48 ], [ 49 ]. Moreover, the long imaging time of the current system configuration further impedes its in-vivo applicability.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization studies on the positioning of multiple detectors have been reported to further improve the SNR based on the anisotropic angular-energy distribution of the Compton scattering photons [ 40 ], [ 41 ], [ 42 ]. Jung et al [ 48 ] and Kim et al [ 49 ] have developed a dynamic dual modality in-vivo XRF imaging system to obtain both the functional and anatomical information on the same imaging bed and to study the accumulation and washout biodistribution of metal nanoparticles in mice. Recently, Moktan et al [ 43 ] and Manohar et al [ 44 ] demonstrated a detection limit of less than 0.3 mg/mL for AuNP using a CdTe (Amptek Inc.) detector coupled with a lead collimator and cone-beam X-rays illuminating the entire 3-cm diameter phantom.…”
Section: Introductionmentioning
confidence: 99%
“…The use of XRF spectrometry for biochemical research has received some interest in this review period. Kim and co-workers 191 combined XRF spectrometry and computed tomography (CT) to investigate the in vivo biodistribution of Au NPs. A transmission CT detector was installed in an existing pinhole XRF instrument, enabling dual detection.…”
Section: Applications: Clinical and Biological Materialsmentioning
confidence: 99%
“…Besides the use of pencil-beam setups with near-monochromatic incident radiation, in vivo biodistribution measurements of gold nanoparticles (GNPs) have also been demonstrated with polychromatic fan-beam X-rays [ 37 ]. The combination of a transmission CT detector installed in an existing pinhole XRF imaging system using a two-dimensional cadmium zinc telluride (CZT) camera allows to acquire functional and anatomic information on the same platform [ 38 ]. The pinhole XRF system used in [ 38 ] comprised a tungsten fan-beam collimator, a lead pinhole collimator and a CZT camera, reaching a spatial resolution of 4.4 mm.…”
Section: Current Status and Recent Promising Developments Of Preclini...mentioning
confidence: 99%
“…The combination of a transmission CT detector installed in an existing pinhole XRF imaging system using a two-dimensional cadmium zinc telluride (CZT) camera allows to acquire functional and anatomic information on the same platform [ 38 ]. The pinhole XRF system used in [ 38 ] comprised a tungsten fan-beam collimator, a lead pinhole collimator and a CZT camera, reaching a spatial resolution of 4.4 mm. Due to the different optimal energy spectra for XRF and CT imaging (high energies above the K-edge of GNPs for XRF and low energies to produce sufficient contrast on CT), images had to be sequentially acquired on the same platform [ 38 ].…”
Section: Current Status and Recent Promising Developments Of Preclini...mentioning
confidence: 99%